STRUCTURING THE ECONOMIC POTENTIAL OF HOSPITALITY INDUSTRY ENTERPRISES - Antoniuk, Kateryna; Vivsiuk, Iryna (European Science, 2024)
In the work, a study of the structuring of the economic potential of hospitality industry enterprises was carried out. The authors determined that when studying the structuring of the economic potential of hospitality industry enterprises, it is worth sta